2020
DOI: 10.1038/s41598-020-65932-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alkaloids in food consumption, metabolism and survival in a blood-sucking insect

Abstract: p = 0.0001, CAF vs. THE, Holm-Sidak = 4.94, p = 0.02). This remarkable effect was only evinced for CAF, which produced significantly more deaths than the AS, QUI, and THE. Also, during the first 40 days the survival curves of AS, QUI and THE groups were not statistically different from each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Plants produce a wide variety of secondary metabolic compounds such as alkaloids that mediate plant-animal interactions (Schoonhoven et al, 2005). These phytochemicals are found in nectar and in plant tissues at different concentrations and, although the dose-dependent role of some of them in attracting and rewarding pollinators has been demonstrated (Wright et al, 2013;Stevenson et al, 2017), they are generally regarded as defence mechanisms to reduce damage from non-adapted phytophagous animals, because they are bitter tasting and toxic (Szentesi and Wink, 1991;Adler, 2000;Thomson et al, 2015;Muñoz et al, 2020;Mustard, 2020). In the context of evolutionary arms race, the complex mechanisms of secondary metabolite production evolved by plant species to resist herbivory have, in return, made herbivores adapt a wide range of mitigation processes of their negative effects (Dearing et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Plants produce a wide variety of secondary metabolic compounds such as alkaloids that mediate plant-animal interactions (Schoonhoven et al, 2005). These phytochemicals are found in nectar and in plant tissues at different concentrations and, although the dose-dependent role of some of them in attracting and rewarding pollinators has been demonstrated (Wright et al, 2013;Stevenson et al, 2017), they are generally regarded as defence mechanisms to reduce damage from non-adapted phytophagous animals, because they are bitter tasting and toxic (Szentesi and Wink, 1991;Adler, 2000;Thomson et al, 2015;Muñoz et al, 2020;Mustard, 2020). In the context of evolutionary arms race, the complex mechanisms of secondary metabolite production evolved by plant species to resist herbivory have, in return, made herbivores adapt a wide range of mitigation processes of their negative effects (Dearing et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of AChE will cause acetylcholine accumulation at the synaptic pathway, disturbing the nerve impulse transmission (Rattan, 2010). Corresponding to this event, the insects exposed to alkaloids will finally have a lack of coordination in their body systems (Hussein et al, 2018), including physiological stress (Muñoz, 2020) and eventually death, as observed in the recent study.…”
Section: Discussionmentioning
confidence: 78%
“…Both taste and smell are important sensory inputs that may signal the quality or content of food. For instance, foods containing potentially harmful secondary metabolites might be avoided as they taste bitter (Muñoz et al 2020). However, some animals rely on these compounds for acquired chemical defenses, such as butterflies that sequester cardenolides and poison frogs that sequester alkaloids (Ruxton et al 2018).…”
Section: Introductionmentioning
confidence: 99%